The Legacy of Vanalombo: Exploring links between Vanalombo and Jako Malabar from the perspective of a Makonde musician and dancer - Nafassi, Vintani (College of Music, 2024)
For this project and dissertation, I examine the performance traditions of Jako musician-dancers from Réunion Island and Vanalombo performers from the Mueda Plateau in Mozambique from a personal perspective as a Makonde musician and dancer versed in these styles. In the process, I explore possible connections between these two performance traditions that can be explained as the result of the slave trade in the Indian Ocean and its impact on the customs and culture of the inhabitants of the Bourbon Islands. The study culminates in the production of a documentary in which Vanalombo masters of initiation rites and Makonde drum players and dancers participated in demonstrations, recordings, and interviews in Makonde settlements around Maputo City in Mozambique. This fieldwork footage is presented in a documentary that, along with the written component of the dissertation, traces my practice-oriented research journey and its culmination in a community presentation of Jako and Vanalombo styles. The dissertation overviews secondary sources on the subject in the fields of ethnomusicology, musicology, and anthropology, as well as archival and museum documentation from Réunion Island, and assembles interviews and conversations with musicians, dancers and elders still actively involved in Jako and Vanalombo performances. As initiated insider and practitioner of Mapiko dance, I have been able to rely on insights drawing on personal experience as a performer and have made auto-ethnographic reflection a central tenet of my approach. From a personal point of view, researching these connections stemmed from an ambition to better understand the historical events that have shaped and are shaping Makonde society in urban contexts and to seek out ways to respond to the challenges of cultural continuity in a fastchanging world.